2006
DOI: 10.1007/s00330-006-0366-3
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of acute pyelonephritis in the adult

Abstract: The diagnosis of acute pyelonephritis in adults is predominantly made by a combination of typical clinical features of flank pain, high temperature and dysuria combined with urinalysis findings of bacteruria and pyuria. Imaging is generally reserved for patients who have atypical presenting features or in those who fail to respond to conventional therapy. In addition, early imaging may be useful in diabetics or immunocompromised patients. In such patients, imaging may not only aid in making the diagnosis of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 42 publications
(46 reference statements)
3
99
0
14
Order By: Relevance
“…Our results showed that the 46 inflammatory foci had statistically lower ADC values (1.43 ± 0.32 9 10 -3 mm 2 /s) than healthy parenchyma, as measured in the 22 patients with suspected APN (2.06 ± 0.16 9 10 -3 mm 2 /s) and in the 26 patients without suspected APN (1.99 ± 0.14 9 10 -3 mm 2 /s). The ADC ability to identify APN foci in transplanted kidneys, as estimated by the ROC curve, was excellent (95% CI for AUC 0.995-1), determining ADC < 1.9 9 10 -3 mm 2 /s as the region typical of APN foci (PPV = 94% and NPV = 100%) The role of diagnostic imaging in confirming a clinical suspicion of APN and its impact on treatment decisions has been reported by several studies [14][15][16][17][18][19]. In particular it was also emphasized that imaging is indispensable for confirming treatment effectiveness during follow-up [20].…”
Section: Discussionmentioning
confidence: 92%
“…Our results showed that the 46 inflammatory foci had statistically lower ADC values (1.43 ± 0.32 9 10 -3 mm 2 /s) than healthy parenchyma, as measured in the 22 patients with suspected APN (2.06 ± 0.16 9 10 -3 mm 2 /s) and in the 26 patients without suspected APN (1.99 ± 0.14 9 10 -3 mm 2 /s). The ADC ability to identify APN foci in transplanted kidneys, as estimated by the ROC curve, was excellent (95% CI for AUC 0.995-1), determining ADC < 1.9 9 10 -3 mm 2 /s as the region typical of APN foci (PPV = 94% and NPV = 100%) The role of diagnostic imaging in confirming a clinical suspicion of APN and its impact on treatment decisions has been reported by several studies [14][15][16][17][18][19]. In particular it was also emphasized that imaging is indispensable for confirming treatment effectiveness during follow-up [20].…”
Section: Discussionmentioning
confidence: 92%
“…Ultrasound can be helpful in identifying the source of infection [8][9][10][11]; it can help define and monitor the hemodynamic status of the patient via evaluation of inferior vena cava, heart and lung water [12][13][14]; it can guide invasive procedures in both diagnosis (sampling) and treatment (drainage) [15].…”
Section: Discussionmentioning
confidence: 99%
“…• To review the pathogenesis of urinary infection, obstruction, and stones • To discuss the imaging features of acute urologic infections such as renal abscess, acute pyelonephritis, and emphysematous pyelonephritis or chronic infections such as renal tuberculosis • To illustrate the imaging of struvite or infection stones as well as highlight their complications only 20% of patients [2,3]. However, new techniques such as tissue harmonics have showed sensitivity and specificity of 97% and 80% [3].…”
Section: Learning Objectivesmentioning
confidence: 99%
“…Following intravenous contrast administration, pyelonephritis manifests as "wedge shaped" or linear regions of decreased enhancement that spans from the renal sinus to the renal cortex. The excretory phase, obtained between 3 and 5 min after the administration of contrast, should be performed in suspected urinary obstruction [2]. CT also can evaluate for additional features of renal inflammation and its complications, including inflammation of the perinephric fat, thickening of Gerota's fascia, and abscess formation.…”
Section: Ct Techniquementioning
confidence: 99%
See 1 more Smart Citation